RUANG LINGKUP ADMINISTRASI DAN MANAJEMEN PENDIDIKAN - Sulis Arieyati; Zain Azizah Zarra; Muhammad Ibnu Saiful; Muhammad Hasan Basari (JIP: Jurnal Ilmu Pendidikan, 2025)
Educational administration and management are two interrelated concepts that contribute to the effective and efficient achievement of educational goals. This article aims to examine the scope of educational administration and management in the context of formal educational institutions, particularly at the school and university levels. Through a literature review approach, this article explores the basic concepts, functions, and differences and interrelationships between educational administration and management. The study findings indicate that educational administration encompasses a broader scope of work, including planning, organizing, directing, supervising, and evaluating educational policies and programs. Meanwhile, educational management focuses more on the process of managing resources such as educators, students, facilities, infrastructure, and finances to optimally achieve educational goals. Furthermore, this article highlights the challenges of implementing educational administration and management in the digital era, such as the demands of utilizing technology in school information systems and the need for adaptive leadership competencies. This study is expected to contribute to broadening the insights of academics and educational practitioners regarding the strategic role of administration and management in improving the quality of education in Indonesia.